Goethite nanorods as a cheap and effective filler for siloxane nanocomposite elastomers1. Issue 56 (19th June 2015) - Iacob, M.; Stiubianu, G.; Tugui, C.; Ursu, L.; Ignat, M.; Turta, C.; Cazacu, M.
<x xml:space="preserve">Abstract</x> Composites based on PDMS and goethite nanorods are for the first time approached from the perspective of dielectric elastomers.